Knowledge, Attitudes, and Practices in Sustainable Nutrition in Late Adulthood- A Qualitative Analysis - Sekhri, Anukrati; Ranawat, Ragini; Jain, Harsha; Lodha, Kritika (Indian Journal of Extension Education, 2025)
Sustainable nutrition is the need of the hour to ensure optimal health without jeopardizing the needs of the upcoming generations. This study, conducted in 2024, investigates the knowledge, attitudes, and practices (KAP) pertaining to sustainable nutrition amongindividuals in late adulthood (above the age of 50). A sample of 20 residents of Jaipur city, above the age of 50 years, was chosen and a qualitative research design was used. In-depth, semi-structured interviews were conducted to understand the participants’ approach as well as knowledge of sustainable nutrition, their dietary habits, food purchasing decisions, and the factors influencing their food choices. The study revealed that participants understand the importance and need of sustainable nutrition practices, yet they do not reflect this sense of responsibility in their choices. The discrepancy between the two owes to multiple factors, including convenience, accessibility issues, and a high purchasing power. The impact of this study extends beyond understanding the behavioural patterns of the individuals in their late adulthood. By identifying the knowledge gaps, efforts can be channelised towards developingeducational programs that encourage wiser, more sensitive, and informed choices among this age group.